The study of probability distributions of intervals remains DST-index values relative to trend line - Приставка, П. О.; Шаповал, Г. А. (Problems of Informatization and Control, 2013)
The article considers the dynamics of geomagnetic activity index DST as a system that describes theprocess of staying in two states relative to the trend line. Investigated the distributions of inter-systemshafts being in certain states. Statistically significant proven that intervals ly balances DST-index valuesare distributed exponentially.